STRENGTHENING BRAND EQUITY THROUGH LOCAL AGENT NETWORKS: EVIDENCE FROM AN INDONESIAN UMRAH TRAVEL - Kevin Maulana (CV. Radja Publika, 2026)
This thesis investigates the erosion of brand equity at PT Maulana Aswaja Barokah (MAB), an emerging Umrah and Hajj travel agency operating in West Java, Indonesia. Despite offering Sharia-compliant pilgrimage services through a decentralized network of local agents, MAB recorded a 43.3% year-on-year decline in customer departures between January–September 2024 and the same period in 2025. The study seeks to examine the underlying drivers of this performance deterioration by evaluating brand equity across four critical dimensions: brand awareness, perceived quality, brand associations, and brand loyalty. Adopting a qualitative case study approach, the research is informed by a preliminary survey involving 12 participants, comprising prospective and former Umrah pilgrims. The analysis is anchored in Aaker’s Customer-Based Brand Equity (CBBE) model, further enriched by external industry diagnostics using PESTEL and Porter’s Five Forces frameworks. The findings suggest that MAB’s brand positioning suffers from weak visibility, fragmented messaging, and inconsistent agent representation at the community level. These deficiencies impair customer trust and impede loyalty development, despite price competitiveness and product adequacy. The study concludes that in culturally embedded service sectors such as religious travel, brand equity is not merely a function of pricing or functional quality but is shaped by trust-building mechanisms, agent credibility, and social legitimacy. Strategic implications include formalizing agent training and brand alignment, amplifying authentic testimonials, and embedding community-based marketing practices. This research contributes to the broader discourse on brand equity by contextualizing established theory within a religious travel setting, offering managerial insights for trust-sensitive and experience-driven markets.